Impact of social responsibility in Financial economic performance of component brazilian companies of Dow Jones Sustainability Index - Vergini, Danielle Paná; Jacomossi, Fellipe André; Turra, Salete; Hein, Nelson (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The aim of this study is to analyze the relationship of social indicators with the financial performance of Brazilian companies listed in the dow jones sustainability index. The paper is characterized as descriptive research with quantitative approach and document analysis. Among eight Brazilian companies belong in go the dow jones sustainability index that are considered socially and environmentally responsible in the new york stock exchange, we obtained a sample of five Brazilian organizations. These companies were observed from 2009 to 2013, performing with the descriptive analysis, chow test, lmbreusch-pagantest, hausman test, as well as panel data regression using the statistical software stata. The results show that the internal social investment impacts negatively on the financial performance of the companies belong in to the dow jones sustainability index. Although no significant relationship between the external social index and the yield variables, the ratio of the coefficient is also negative. For investments in the environment the relationship was significant only with the variable profitability of total assets.